EVALUASI PROSES BANTUAN PROGRAM KELUARGA HARAPAN (PKH) DI KELURAHAN MALALAYANG SATU KECAMATAN MALALAYANG KOTA MANADO - Stevianus ., Laoh; Martha M. Sendow; Melissa L.G. Tarore (AGRI-SOSIOEKONOMI, 2016)
The objective of research is to examines and to describe evaluate the PKH already right targets, and how commitment or obligation carried out by the PKH, and if the help of cash who received by PKH used to the education and health needs or to the other needs. Data analysis was done descriptively, served with using the table and then be interpreted. This research was conducted from March 2016 until June 2016 started from preparation until report compilation. The data used in the form of primary data and secondary data in which 8 respondent of the population. This research was carried out with purposive sampling method. The result showed that participants of PKH in Malalayang Satu village is almost right target based on SLB and social ministry criteria but the participants of PKH less run commitment also the help of cash received by the PKH used to the other needs than education and health.